환경정책, 재분배정책, 경제성장에 관한 정치경제학적 분석 - 김재훈 (12006, 2011)
We analyse an overlapping generation model in which economic agents, especially their income distribution, influence environmental policy and redistributive policy through political decision making process. In an economic equilibrium which doesn't conside